Perceptual motor test for children 5-6 years old - Yudanto Yudanto; Abdul Mahfudin Alim; Ahmad Nasrulloh (Jurnal Keolahragaan, 2021)
This research and development aims to produce perceptual motor tests for children aged 5-6 years. The development procedure adapted the Borg and Gall model, namely: (1) the preliminary study and planning stage, (2) the product development stage, (3) the expert validation stage, 4) the trial phase, and (5) product revision. The trial subjects used 10 children aged 5-6 years. The data used in this research are quantitative and qualitative data. Quantitative data were obtained from the results of the validation of the perceptual motor test draft and trials. Qualitative data obtained from the results of a questionnaire in the form of input and suggestions from material experts and practitioners. The data collection instrument used questionnaire guidelines. The questionnaire was used to get input from material experts and practitioners. The product can be said to be accepted and used must be tested for validity and reliability. Material expert validation test based on content validity and reliability testing using observation reliability with Alpha Cronbach. The results of the product developed show that perceptual motor tests for children aged 5-6 years are acceptable and in accordance with aspects of perceptual motor elements. The reliability test result was 0.930.